x+(2x+5)+(2x+5)=95

Simple and best practice solution for x+(2x+5)+(2x+5)=95 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+(2x+5)+(2x+5)=95 equation:


Simplifying
x + (2x + 5) + (2x + 5) = 95

Reorder the terms:
x + (5 + 2x) + (2x + 5) = 95

Remove parenthesis around (5 + 2x)
x + 5 + 2x + (2x + 5) = 95

Reorder the terms:
x + 5 + 2x + (5 + 2x) = 95

Remove parenthesis around (5 + 2x)
x + 5 + 2x + 5 + 2x = 95

Reorder the terms:
5 + 5 + x + 2x + 2x = 95

Combine like terms: 5 + 5 = 10
10 + x + 2x + 2x = 95

Combine like terms: x + 2x = 3x
10 + 3x + 2x = 95

Combine like terms: 3x + 2x = 5x
10 + 5x = 95

Solving
10 + 5x = 95

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + 5x = 95 + -10

Combine like terms: 10 + -10 = 0
0 + 5x = 95 + -10
5x = 95 + -10

Combine like terms: 95 + -10 = 85
5x = 85

Divide each side by '5'.
x = 17

Simplifying
x = 17

See similar equations:

| y+8=-4(x+7) | | y=(x)2-2 | | 3(4y-3)=7 | | h(t)=150t-5t | | 4-6(x-4)=2(x-4) | | 8x-92=5x-8 | | 2(-5a^2+8a-12)-(a^2-3a-7)= | | 3-(8x+6)=3 | | 0x-3=0 | | 0y-3=0 | | 4x-8-3(x-5)=3(x-1) | | y-15=32 | | -11nk^2+5nk-6y=0 | | 2[1-3(x+2)]=-x | | 54-4x=14x+22 | | 2d-17=3d+8 | | 3(y+7)+4=43 | | 142-7x=20x+22 | | q+3q=2q-6 | | x+1=-15 | | -4r+5=-3r+9 | | 3(-8x)+8=80 | | 3z-3(1-z)=z-17 | | -8h-1=-33 | | 9(y-4)-3y=6(y-6) | | 90+4x+x=180 | | 15=-2p+27 | | -6(-x-10)=10(-x-10) | | 8x-9x=73-82 | | 0.50x+0.15(70)=48.5 | | 35+x=18 | | -7(3a+10)=0 |

Equations solver categories